1988
DOI: 10.1093/ajcn/47.5.848
|View full text |Cite
|
Sign up to set email alerts
|

Methanol production from the degradation of pectin by human colonic bacteria

Abstract: When ingested, pectin can lower serum cholesterol levels in humans. Pectin is degraded by fecal bacteria in the colon. We examined the release of methanol (MeOH) by this degradation. A 0.2% glucose (2 g/L) mixture was used as the control medium. A pure culture of pectinolytic Erwinia carotovora was the control bacterium. The chief substrates were, in set 1, 0.2% pectin (2 g/L) and, in set 2, 0.1% glucose (1 g/L) and 0.1% pectin (1 g/L). Cultures of fecal bacteria and E carotovora grew for 72 h in each of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Methanol has been shown to be produced from pectins by human colonic bacteria in uitro (Siragusa et al 1988). We have also found that PCW polysaccharides are extensively degraded in the rat gut.…”
Section: Discussionmentioning
confidence: 57%
“…Methanol has been shown to be produced from pectins by human colonic bacteria in uitro (Siragusa et al 1988). We have also found that PCW polysaccharides are extensively degraded in the rat gut.…”
Section: Discussionmentioning
confidence: 57%
“…Fumarate and succinate are the intermediates of propionate production from carbohydrates through the succinate pathway, which explains the reduced concentrations of these two metabolites. Human colonic bacteria also produce methanol via the degradation of pectins, which are a class of heterogeneous polysaccharides and can be found in the inter-and intra-cell walls of most fruits and vegetables 23 . Higher concentrations of methanol were found after 5-h room temperature storage, which indicate that fecal bacteria were able to further degrade indigestible dietary components when samples were stored at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Even if one avoids aspartame-bearing products, normal dietary exposure to methanol may still occur from consumption of certain fruits, vegetables and juices with high pectin content (i.e., direct ingestion; Butchko and Kotsonis, 1991;Frenkel et al, 1998). Furthermore, though some of the pectin content is converted directly to methanol in these food products, unprocessed pectin can itself be converted in the gut to methanol by the actions of local bacteria (i.e., another indirect form of ingestion; Siragusa et al, 1988;Lindenger et al, 1997), again resulting in substantive daily increases in blood methanol content.…”
Section: Introductionmentioning
confidence: 99%